2017
DOI: 10.1186/s13063-017-2267-y
|View full text |Cite
|
Sign up to set email alerts
|

Framing the conversation: use of PRECIS-2 ratings to advance understanding of pragmatic trial design domains

Abstract: BackgroundThere continues to be debate about what constitutes a pragmatic trial and how it is distinguished from more traditional explanatory trials. The NIH Pragmatic Trials Collaborative Project, which includes five trials and a coordinating unit, has adopted the Pragmatic-Explanatory Continuum Indicator Summary (PRECIS-2) instrument. The purpose of the study was to collect PRECIS-2 ratings at two points in time to assess whether the tool was sensitive to change in trial design, and to explore with investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Johnson KE [ 15 ] pointed out that evaluators struggled to use the PRECIS system for analysis, as large differences existed in inter-evaluator reliability. Furthermore, El DR et al [ 16 ] indicated that the clinical expertise of the investigator also affected scoring in each domain of PRECIS-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson KE [ 15 ] pointed out that evaluators struggled to use the PRECIS system for analysis, as large differences existed in inter-evaluator reliability. Furthermore, El DR et al [ 16 ] indicated that the clinical expertise of the investigator also affected scoring in each domain of PRECIS-2.…”
Section: Discussionmentioning
confidence: 99%
“…We propose several suggestions: 1) More research is urgently needed to establish the easiest and most useful tool to facilitate the applicability of results in clinical practice, distinguish between effectiveness and efficacy results and assist researchers in preparing and planning clinical trials; [ 16 ] 2) Researchers should pay attention to PRECIS-2 before they design RCTs and promote self-review during their implementation. 3) Due to the large number of Chinese researchers, the PRECIS-2 guidelines should be translated into Chinese; Related introductory articles should also be published in Chinese to promote a wider range of applications for PRECIS-2; 4) Journals all over the world that publish clinical trials should require authors to include a quantitative score related to the effectiveness or efficacy of their combined research articles; [ 16 18 ] 5) Several issues specific to CHM should be clarified in the new version of PRECIS. For flexibility (delivery), how do we define “a highly specified, protocol driven intervention” and “permitted co-interventions” in CHM, as doctors of Chinese medicine add or subtract herbs based on syndrome differentiation at different times?…”
Section: Discussionmentioning
confidence: 99%
“…We have also learned that our postdischarge telephone calls have made no difference in rates of readmission or patient-experience ratings, that our appointment-reminder letters were completely ineffective, and that our community health worker program was inadvertently targeting patients who were unlikely to benefit" [20]. The most desirable features of A/B experiments are their large-scale and low cost, which are commensurate with the tradition of large simple trials [42] and the emerging interest in pragmatic trials [43,44]. Lower costs would allow to test more and other interventions and provide better evidence on thus far understudied healthcare questions [13,16].…”
Section: Similarities and Dissimilarities With Medical Rctsmentioning
confidence: 95%
“…A pragmatic [34], parallel-group, double-blind, randomized controlled trial (Table 3) will be conducted. We will enroll 60 patients who are admitted to the ICU at a university hospital in Tehran, Iran.…”
Section: Interventionmentioning
confidence: 99%